Determination of an acceptable comfort zone for apartment occupants in South Korea: An empirical analysis of cooling operation. (15th November 2017) - Ryu, Ji Hye; Hong, Won Hwa; Seo, Hyun Cheol; Seo, Youn Kyu
Abstract: Occupants of apartment blocks tend to wear less clothing and exhibit lower metabolic rates than occupants of other building types. Further, the use of air conditioning systems to maintain certain comfort levels within living spaces automatically generates financial cost. Therefore, in this study, an acceptable comfort range that differs from the conventional normative comfort range was established. A thermal comfort control method was designed to satisfy both the economic and comfort requirements, and experiments were conducted accordingly. Subsequently, empirical data on cooling were obtained via surveys and measurements and employed to derive regression equations for the thermal sensation vote, comfort sensation vote, and percentage dissatisfaction, which indicate occupant comfort. The derived regression equations were used to graph the comfort range, and the overlap region was plotted on a psychrometric chart to enable identification of an acceptable comfort zone. The suggested acceptable comfort zone, which applies to apartment blocks in Korea, is outside the conventionally recommended comfort zone and can satisfy various occupant preferences, contribute to reducing energy consumption, and facilitate maintenance of comfortable living environments. Highlights: Empirical cooling data were used to derive regression equations for occupant comfort. The thermal and comfort sensation votes and percent dissatisfaction were analyzed. A thermal control method meeting economic and comfort requirements was established. An acceptable thermal comfort range for Korean apartments was identified empirically. This range can reduce energy consumption and satisfy various occupant preferences.